Patterns of glioblastoma treatment and survival over a 16-years period: pooled data from the German Cancer Registries - Efremov, Ljupcho; Abera, Semaw Ferede; Bedir, Ahmed; Vordermark, Dirk; Medenwald, Daniel (Journal of cancer research and clinical oncology, 2021)
Introduction Glioblastoma multiforme (GBM) is a primary malignant brain tumour characterized by a very low long-term survival. The aim of this study was to analyse the distribution of treatment modalities and their effect on survival for GBM cases diagnosed in Germany between 1999 and 2014. Methods Cases were pooled from the German Cancer Registries with International Classification of Diseases for Oncology, third edition (ICD-O-3) codes for GBM or giant-cell GBM. Three periods, first (January 1999–December 2005), second (January 2006–December 2010) and a third period (January 2011–December 2014) were defined. Kaplan–Meier plots with long-rank test compared median overall survival (OS) between groups. Survival differences were assessed with Cox proportional-hazards models adjusted for available confounders. Results In total, 40,138 adult GBM cases were analysed, with a mean age at diagnosis 64.0 ± 12.4 years. GBM was more common in men (57.3%). The median OS was 10.0 (95% CI 9.0–10.0) months. There was an increase in 2-year survival, from 16.6% in the first to 19.3% in the third period. When stratified by age group, period and treatment modalities, there was an improved median OS after 2005 due to treatment advancements. Younger age, female sex, surgical resection, use of radiotherapy and chemotherapy, were independent factors associated with better survival. Conclusion The inclusion of temozolomide chemotherapy has considerably improved median OS in the older age groups but had a lesser effect in the younger age group of cases. The analysis showed survival improvements for each treatment option over time.